Hubungan K-pop Idol Sebagai Brand Ambassador terhadap Keputusan Pembelian Followers - Santy Widiadamayanti; Indri Rachmawati (Bandung Conference Series: Communication Management, 2022)
Abstract. Competition to attract consumers to companies in Indonesia is getting tougher, especially for marketplace companies. Various ways are carried out by companies to increase consumers, one of which is making Kpop Idol as a Brand Ambassador. This study takes the title "The Relationship of Kpop Idol as a Brand Ambassador to Followers Purchasing Decisions" in order to determine the relationship of the Kpop Idol brand ambassador in the WIB TV Show Tokopedia advertisement to increase purchasing decisions on followers of the @Tokopedia account on Twitter. The research method using correlational quantitative. The theory used in this study is the theory of Agenda Setting. Data collection techniques used in this study were through interviews, distributing questionnaires or questionnaires, observation and literature studies. The population used in this study were followers of the @Tokopedia account on Twitter with a sample return technique, namely the random sampling technique. The purpose of this study was to determine the relationship between brand ambassadors and the variables of transference, congruence, credibility, attractiveness and power towards purchasing decisions for followers of the @Tokopedia account on Twitter. The results in this study are that there is a strong relationship between Kpop idol brand ambassadors and purchasing decisions for followers of the @Tokopedia account on Twitter. Abstrak. Persaingan untuk menarik konsumen pada perusahaan di Indonesia semakin ketat terutama bagi perusahaan marketplace. Berbagai cara dilakukan oleh perusahaan demi meningkatkan konsumen salah satunya menjadikan Kpop Idol sebagai Brand Ambassador. Pada penelitian ini mengambil judul “Hubungan Kpop Idol sebagai Brand Ambassador Terhadap Keputusan Pembelian Followers” guna mengetahui hubungan brand ambassador Kpop Idol dalam iklan WIB TV Show Tokopedia terhadap meningkatkan keputusan pembelian pada followers akun @Tokopedia di Twitter. Adapun metode penelitian ini yang menggunakan kuantitatif korelasional. Teori yang digunakan dalam penelitian ini adalah teori agenda setting. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah melalui wawancara, menyebarkan angket atau kuesioner, observasi dan studi Pustaka. Populasi yang digunakan dalam penelitian ini adalah followers akun @Tokopedia di Twitter dengan Teknik pengembalian sampel yaitu Teknik random sampling. Tujuan penelitian ini, untuk mengetahui hubungan brand ambassador dengan variabel transference, congruence, kredibilitas, daya tarik dan power terhadap keputusan pembelian followers akun @Tokopedia di Twitter. Hasil dalam penelitian ini adalah terdapat hubungan kuat antara brand ambassador Kpop idol dengan keputusan pembelian followers akun @Tokopedia di Twitter.